Wind Resource Estimation and Mapping at Ali Al-Gharby Site (East-South of Iraq) Using WAsP Model - K. Resen, Ali (Iraqi Journal of Science, 2023)
The wind atlas analysis and application program, WAsP, is used to assess windenergy potential، wind climate from geostrophic winds of a given area. In this paper,metrological data from Ali Algharby station was used to predict the wind resourceand wind turbine energy production at Ali Algharby site.Data from metrological station was used to draw up observed wind climates at theanemometer site. Site contour map was digitized using WAsP Map Editortool.Observed wind climate, digitized contour map, terrain roughness length, obstaclegroups and their porosity were used as input to the WAsP model. Vestas V182, 1.65MW turbine was used. Weibull probability distribution graph of wind speed, powerdensity were drawn. A directional wind rose for January to December 2011 weredrawn for site. Results showed that the studied area have Annual Energy Production(AEP) about 5 GWh as mean value. The calculation was obtained at 70 m hubheight for the turbine and the roughness length (0.0, 0.03, 0,1,0,4, 1.5) m for theselected area.